Better to Own or to Regulate? The Case of Alcohol Distribution and Sales. (February 2017) - Zullo, Roland
Alcohol-related income generation is compared across monopoly and license off-premise alcohol regulatory models in U.S. states, 1977-2010. An optimum organizational-ownership mix is found when states directly own alcohol wholesale and employ a network of state-owned retailers serving urban regions and private agents serving less-populated regions. Per capita alcohol-related income in US dollars for these optimal systems was $58.82 compared with $26.72 with license systems. This disparity held after controlling for alcohol sales and retail hours of operation. The findings challenge the wisdom of asset divestment as a response to fiscal stress and contradict a central tenet of New Public Management (NPM) Theory.